Recognition of shorter and longer trimethyllysine analogues by epigenetic reader proteins - Al Temimi, A; Belle, R; Kumar, K; Poater, J; Betlem, P; Pieters, B; Paton, R; Bickelhaupt, F; Mecinović, J (Royal Society of Chemistry, 2018)
Histone Nε-lysine methylation is a widespread posttranslational modification that is specifically recognised by a diverse class of Nε-methyllysine binding reader proteins. Combined thermodynamic data, molecular dynamics simulations, and quantum chemical studies reveal that reader proteins efficiently bind trimethylornithine and trimethylhomolysine, the simplest Nε-trimethyllysine analogues that differ in the length of the side chain.